2018
DOI: 10.25186/cs.v13i3.1452
|View full text |Cite
|
Sign up to set email alerts
|

CONTRIBUTION OFAGRONOMIC TRAITS TO THE YIELD OF Coffea canephora PIERRE EX A. FROEHNER HULLED COFFEE

Abstract: The evaluation of morphological characters related to the hulled coffee yield subsidizes the selection of <em>Coffea canephora</em> plants that combine a set of favorable traits. The aim of this study was to evaluate the direct and indirect effects of agronomic traits on the production of hulled coffee to subside the plant selection. To this, nine morphological descriptors were evaluated of 130 clones of the botanical varieties Conilon and Robusta over two crop years in the experimental field of Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Analyzing the factors obtained, it can be observed that although the superior performance of C. canephora coffee trees with hybrid characteristics between the botanical varieties Conilon and Robusta is known, few studies have sought to better understand the expression of the characteristics associated with the production of this coffee tree. When interpreting estimates of direct and indirect effects of secondary traits in relation to the main trait -bean yield - Spinelli et al (2018) observed that the number of plagiotropic branches and the number of rosettes per productive branch were the characteristics with the greatest direct effect on the processed coffee yield. Positive associations between the number and length of productive branches were also observed by Ferrão et al (2007), who considered estimates of simple and partial, unstructured correlations.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the factors obtained, it can be observed that although the superior performance of C. canephora coffee trees with hybrid characteristics between the botanical varieties Conilon and Robusta is known, few studies have sought to better understand the expression of the characteristics associated with the production of this coffee tree. When interpreting estimates of direct and indirect effects of secondary traits in relation to the main trait -bean yield - Spinelli et al (2018) observed that the number of plagiotropic branches and the number of rosettes per productive branch were the characteristics with the greatest direct effect on the processed coffee yield. Positive associations between the number and length of productive branches were also observed by Ferrão et al (2007), who considered estimates of simple and partial, unstructured correlations.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen previously selected genotypes (Oliveira et al, 2018b;Spinelli et al, 2018) were evaluated by the following morphological and productive traits: plant height, number of productive plagiotropic branches, distance between rosettes of the plagiotropic branch, number of coffee beans per rosette, number of rosettes per plagiotropic branch, length of plagiotropic branch, length and width of leaves, number of days for fruit ripening and coffee bean size. The genotypic value of production was estimated based on production of hulled coffee using the BLUP (Best Linear Unbiased Prediction) method (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Understood as the genetic potential of the plant to transform energy from the sun to coffee beans, coffee plant yield (measured in bags of coffee grains per hectare) is an important characteristic in development of new cultivars (FERRÃO et al, 2008;RAMALHO et al, 2016, SPINELLI et al, 2018. The Coffea canephora species has two distinct botanical varieties (CHARRIER & BERTHAUD, 1988;DAVIS et al, 2006, MUSOLI et al, 2009 that are grown in the Western Amazon region:the Conilon botanical variety, characterized by plants of bush-type growth, drought tolerance, and greater susceptibility to diseases; and the Robusta botanical variety, characterized by upright growth, larger sized fruit and leaves, lower drought tolerance, and greater resistance to pests and diseases (ROCHA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%